2005
DOI: 10.1007/s00267-005-2776-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Characteristics and Importance of Woody Biomass Resources on the Rural-Urban Fringe in Botswana

Abstract: This article examines the utilization characteristics and importance of woody biomass resources in the rural-urban fringe zones of Botswana. In the literature for Africa, attention has been given to the availability and utilization of biomass in either urban or rural environments, but the rural-urban fringe has been neglected. Within southern Africa, this neglect is not justified; the rural-urban fringe, not getting the full benefits available in urban environments in Botswana, has developed problems in woody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…In the developing world, research has clearly demonstrated that poor urban communities make use of products from trees and other plants growing in or at the fringe of urban areas. Examples range from several studies in South Africa [20,31] to towns in Zimbabwe [34], Botswana [35], Tanzania and Cameroon [21]; Kampala in Uganda [4], Santa Cruz in Bolivia [36], and Bangalore in India [37]. The plants or plant parts that these studies show are commonly collected have a wide range of uses, including: berries or fruit for home consumption or sale; leaves, roots, and bark for medicines; poles for construction; and reeds for craft.…”
Section: Emerging Themes Of Urban Foragingmentioning
confidence: 99%
“…In the developing world, research has clearly demonstrated that poor urban communities make use of products from trees and other plants growing in or at the fringe of urban areas. Examples range from several studies in South Africa [20,31] to towns in Zimbabwe [34], Botswana [35], Tanzania and Cameroon [21]; Kampala in Uganda [4], Santa Cruz in Bolivia [36], and Bangalore in India [37]. The plants or plant parts that these studies show are commonly collected have a wide range of uses, including: berries or fruit for home consumption or sale; leaves, roots, and bark for medicines; poles for construction; and reeds for craft.…”
Section: Emerging Themes Of Urban Foragingmentioning
confidence: 99%
“…Over the past several decades, researchers have explored the links between fuel use, deforestation, and energy poverty in developing countries, largely focusing on the hypothesis that biomass fuel harvesting is a driver of deforestation and degradation. Research addressing the sustainable harvest of fuelwood and other sources of woody biomass falls into two groups: the first asserting that fuelwood harvesting is a major contributor to global forest degradation and has severe negative environmental ramifications (e.g., Eckholm, 1975); and the second asserting that the impacts of non-commercial fuelwood harvesting are not necessarily negative, and that harvesting can sometimes even improve environmental robustness (Arnold et al, 2005; Foley et al 2005; Masera et al, 2006; Nkambwe and Sekhwela, 2006; Naughton-Treves et al, 2007; Openshaw, 2011). In many rural areas, gathering wood for fuel has been shown to not have a detrimental impact on land, but in more densely populated areas where natural resources are less abundant, the demand for land and resources can lead to higher degree of degradation (Nkambwe and Sekjwela, 2006).…”
Section: Linking Biomass Supply To Health Outcomesmentioning
confidence: 99%
“…Barnes et al, (2002) estimate that the absolute number of people dependent on biomass fuels will increase through 2030, suggesting that policy makers should be attentive to factors that influence the supply, demand and distribution of biomass fuels. These trends are particularly striking in sub-Saharan Africa where the consumption of biomass fuels is higher than in any other region (Arnold et al, 2005; Bailis et al, 2005; Nkambwe and Sekhwela, 2006; Vlosky and Smithhart, 2011). East Africa is particularly dependent on biomass fuels; more than 95% of the populations of Burundi, Ethiopia, Rwanda, Tanzania and Uganda use solid fuels for cooking and heating (WHO, 2006; GACC, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Local natural resources, frequently termed non-timber forest products (NTFPs), significantly contribute to daily livelihood needs and income of Africans, both across the rural-urban divide [16][17][18][19][20] and across income levels [11,21,22]. NTFPs are infinitely diverse in their sources [23], however, common uses include food, medicine, cooking fuel, and materials for household construction and marketable craftwork [24][25][26].…”
Section: Introductionmentioning
confidence: 99%